2013
DOI: 10.1021/ja310180c
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Nicotinamide. The Transition-State Structure of Human Nicotinamide Phosphoribosyltransferase

Abstract: Human nicotinamide phosphoribosyltransferase (NAMPT) replenishes the NAD pool and controls the activities of sirtuins (SIRT), mono- and poly-(ADP-ribose) polymerases (PARP) and NAD nucleosidase (CD38). The nature of the enzymatic transition-state (TS) is central to understanding the function of NAMPT. We determined the TS structure for pyrophosphorolysis of nicotinamide mononucleotide (NMN) by kinetic isotope effects (KIEs). With the natural substrates, NMN and pyrophosphate (PPi), the intrinsic KIEs of [1′-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 47 publications
1
53
0
2
Order By: Relevance
“…Several research groups have characterized the structural and enzymological features of mammalian NAMPT. [24][25][26][27][28][29][30][31] Structural and mutagenesis studies have shown that mutations in NAMPT that impair dimerization attenuate enzymatic activity; 26 furthermore, Asp219 is important in defining the substrate specificity of NAMPT, 29 which does not include nicotinic acid. 14,32 Autophosphorylation of NAMPT (by use of ATP) at His247 24,26 creates a reaction intermediate that is hydrolysed during each catalytic cycle, which increases the affinity of NAMPT for NAM and its enzymatic activity up to 1,000-fold.…”
Section: Physiological Role Of Namptmentioning
confidence: 99%
“…Several research groups have characterized the structural and enzymological features of mammalian NAMPT. [24][25][26][27][28][29][30][31] Structural and mutagenesis studies have shown that mutations in NAMPT that impair dimerization attenuate enzymatic activity; 26 furthermore, Asp219 is important in defining the substrate specificity of NAMPT, 29 which does not include nicotinic acid. 14,32 Autophosphorylation of NAMPT (by use of ATP) at His247 24,26 creates a reaction intermediate that is hydrolysed during each catalytic cycle, which increases the affinity of NAMPT for NAM and its enzymatic activity up to 1,000-fold.…”
Section: Physiological Role Of Namptmentioning
confidence: 99%
“…2022 In every case, these transition states were studied from the direction of nucleoside monophosphate pyrophosphorolytic cleavage from the base and phosphorylated ribosyl groups. For orotate phosphoribosyltransferases, insignificant isotope effects were observed with pyrophosphate as the substrate, but use of phosphonoacetic acid, a slow-reacting analogue of pyrophosphate, permitted measurement of the KIE values.…”
mentioning
confidence: 99%
“…Both eukaryotic and prokaryotic sirtuins are known for post-translational modifications using NAD + as a co-substrate. Specifically, deacetylation of acetyl-lysine by the sirtuins produces nicotinamide as a byproduct, which can also be recycled for NAD + biosynthesis as mentioned above (Burgos et al, 2013). Deacetylation of acetyl-lysine has been strongly correlated with the activation of acetyl-coA synthetase ( ACS ) in prokaryotes, which is characterized as a Sir2-dependent enzyme (Starai, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…By being obligate parasites, bacteriophages are known to carry genes toward their own benefit (Gazzaniga et al, 2009) for host metabolic manipulation. Sirtuins are able to deacetylase acetyl-lysine in proteins (Burgos et al, 2013) and their presence in large bacteriophage genomes is still enigmatic. It is natural for phages to carry molecular tools for metabolic reprogramming of their host, since they need them in order to replicate their genome, before capsid packaging.…”
Section: Introductionmentioning
confidence: 99%